Transgenic Kalanchoë blossfeldiana, Containing Individual rol Genes and Open Reading Frames Under 35S Promoter, Exhibit Compact Habit, Reduced Plant Growth, and Altered Ethylene Tolerance in Flowers - Favero, Bruno Trevenzoli; Tan, Yi; Lin, Yan; Hansen, Hanne Bøge; Shadmani, Nasim; Xu, Jiaming; He, Junou; Müller, Renate; Almeida, Aldo; Lütken, Henrik (Frontiers in Plant Science, 2021)
Reduced growth habit is a desirable trait for ornamental potted plants and can successfully be obtained through Rhizobium rhizogenes transformation in a stable and heritable manner. Additionally, it can also be obtained by transformation with Agrobacterium tumefaciens harboring specific genes from R. rhizogenes. The bacterial T-DNA harbors four root oncogenic loci (rol) genes and 14 less known open reading frames (ORFs). The four rol genes, i.e. rolA, rolB, rolC and rolD, are conceived as the common denominator for the compact phenotype and the other less characterized ORFs seem auxiliary but present a potential breeding target for less aberrant and/or more tailored phenotypes. In this study, Kalanchoë blossfeldiana 'Molly' was transformed with individual rol genes and selected ORFs in 35S overexpressing cassettes to comprehensively characterize growth traits, gene copy and expression, and ethylene tolerance of the flowers. An association of reduced growth habit, e.g. height and diameter, was observed for rolB2, ORF13a-2 and ORF14-2 when a transgene single copy and high gene expression were detected. Chlorophyll content was reduced in overexpressing lines compared to wild type (WT), except for one ORF13a (a truncated ORF13a, where SPXX DNA-binding motif is absent). The flower number severely decreased in the overexpressing lines compared to WT. The anthesis timing showed that WT opened the first flower at 68.9±0.9 days and the overexpressing lines showed similar or up to 24 days delay in flowering. In general, a single or low relative gene copy insertion was correlated to higher gene expression, ca. 3 to 5-fold, in rolB and ORF13a lines, while in ORF14 such relation was not directly linked. The increased gene expression observed in rolB2 and ORF13a-2 contributed to reducing plant growth and a more compact habit. Tolerance of detached flowers to 0.5 µL L-1 ethylene was markedly higher for ORF14 with 66% less flower closure at day 3 compared to WT. The subcellular localization of rolC and ORF13a was investigated by transient expression in N. benthamiana and confocal images showed that rolC and ORF13a are soluble and localize in the cytoplasm being able to enter the nucleus.